Transformation-driven reorganization of cross-domain microbial interactomes reflects multifunctionality loss in alpine wetlands - Awais Iqbal; Muhammad Maqsood Ur Rehman; Abraham Allan Degen; Salman Khan; Zhanhuan Shang (Soil Ecology Letters, 2026)

AM fungal and rhizobacteria jointly enhance vegetable waste decomposition in soils and harvest environmental and agronomic benefits in dryland - Muhammad Maqsood Ur Rehman; Sidra Khattak; Ling Zhao; Yun-Li Xiao; Ying Zhu; Awais Iqbal; Rafi Ullah; Nang Chang; Muhammad Abrar; Jian-Ming Li; Hao Sun; Adnan Khan; et al. (Agriculture, Ecosystems & Environment, 2026)

Comprehensive analysis of rock-mud filtrate interactions at elevated temperatures: Implications for drilling and reservoir management in oil and gas industry - Imtiaz Ali; Maqsood Ahmad; Muhammad Yasir (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Integrated evaluation of salt tolerance in cigar tobacco (Nicotiana tabacum L.) varieties for sustainable cultivation in saline environments - Munib Ahmad; Uzair Ullah; Muhammad Ateeq; Shah Zeb Khan; Saeed Ullah; Shaista Jabeen; Maqsood Ul Hassan; Sadam Khan; Pingping Wang; Suiling Ai; Lixin Zhang (Journal of Environmental Management, 2026)

Correction to: Tracing Potentially Toxic Metals from Water to Soil, Maize, and Cow Milk: Food Chain Risks and Safety Concerns - Kafeel Ahmad; Mashal Maqsood; Zafar Iqbal Khan; Asma Ashfaq; Mutiya Zafar; Muhammad Mazhar Iqbal; Ijaz Rasool Noorka; Hafsa Memona; Farzana Siddique; Ilker Ugulu (Bulletin of Environmental Contamination and Toxicology, 2026)

Combined effects of ridge-furrow plastic mulching and organic-inorganic fertilization on soil organic carbon and crop yield in dryland agroecosystem - Rafi Ullah; Xu-Long Zhang; Abdul Qadir Khan; Muhammad Maqsood Ur Rehman; Hailong Ma; Chaoli Guo; Feng-Min Li (Agriculture, Ecosystems & Environment, 2026)

Alleviation of salinity induced toxicity in quinoa (Chenopodium quinoa Willd.) through ascorbic acid application - Muhammad Faisal Maqsood; Tahira Fatima; Rehana Kanwal; Fozia Farhat; Muhammad Shahbaz; Muhammad Jamil; Saba Shafqat; Muhammad Asif; Muhammad Hamza Maqsood; Maryam Tariq; Usman Zulfiqar; Muhammad Ahmad (Biocatalysis and Agricultural Biotechnology, 2026)

Sustainable approaches to alleviate salinity stress in two fenugreek cultivars through moringa leaf extract and salicylic acid - Sumreen Anjum; Iqra Tabassam; Mubeen Sarwar; Tanveer Hussain; Shoaib ur Rehman; Sumaira Maqsood; M. Irfan Ashraf; Muhammad Ashfaq; Qurban Ali (Plant Biosystems, 2026)

Impact of insect socialism on the ecology and management of ambrosia beetles - Neslihan Gültekin; Melek Güçlü; Dilbar Hussain; Sumaira Maqsood; Levent Gültekin; Muhammad Qasim (Arthropod-Plant Interactions, 2026)

Evaluation of host suitability and larval instar effects on the reproductive potential of entomopathogenic nematodes against lepidopteran pests - Hina Safdar; Sumaira Maqsood; Salman Ghuffar; Aftab Ahmad; Muhammad Hafeez; Hifza Safdar; Tauseef Anwar; Huma Qureshi; Hossam S. El-Beltagi; Ibrokhim Ismoilov; Feruza Tukhtaboeva; Nazih Y. Rebouh; et al. (Crop Protection, 2026)

Biogas upgrading technologies with emphasis on membrane separation performance - Junaid Ahmad; Rizwan Nasir; Muhammad Faheem; Mustafa Alsaady; Khuram Maqsood; Chawalit Ngamcharussrivichai (Biomass and Bioenergy, 2026)

Multilevel barriers to antimicrobial stewardship in tertiary care hospitals: A comparative systematic scoping review of high-income versus low-/middle-income countries evidence mapped by study design and healthcare professionals - Azfar Athar Ishaqui; Zikria Saleem; Tauqeer Hussain Mallhi; Sultan M. Alshahrani; Khalid Orayj; Salman Ashfaq Ahmad; Rayah Asiri; Emad Ali Alsaleh; Muhammad Imran; Mohammed Ali Kaddoura; Bilal Jawed; Narendar Kumar; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Genomic characterization of an isolate of tomato leaf curl New Delhi virus associated with tomato crops - Abdul Majid; Muhammad Taimoor Shakeel; Muhammad Naveed Aslam; Ambreen Maqsood; Muhammad Raheel; Waqas Ashraf; Tahir Farooq; Atta ur Rehman Khan; Mahmoud Ahmed Amer; Mohammed Ali Al-Saleh (European Journal of Plant Pathology, 2026)

Correction to: Diversity of wild Morchella (Ascomycota) revealed by integrated morphological and molecular analyses - Sania Shoukat; Nasir Mehmood; Salman Ghuffar; Sadiqa Bibi; Muhammad Rauf; Gulshan Irshad; Gule-e-Lalah Khan; Sumaira Maqsood; Tauseef Anwar; Huma Qureshi; Nazih Y. Rebouh; Salohiddinjon Yunusov; et al. (Folia Microbiologica, 2026)

Effect of split applications of silicon nanoparticles and conventional sources of Si on growth, antioxidant enzymes, and cadmium uptake in wheat under Cd stress - Muhammad Aamer Maqsood; Nimra Ashraf; Muhammad Zia-ur-Rehman; Muhammad Usman; Muhammad Rizwan; Hesham F. Alharby; Amnah M. Alamri; Refaat A. Abohassan (South African Journal of Botany, 2026)

Microplastics as Trojan horses: Vectors of pathogens, pollutants, and antimicrobial resistance genes - Ghazala Saeed; Ali Afzal; Afzal Nimra; Zaira Ahmad; Amna Rehman; Kaleem Maqsood; Tayyba Jan; Muhammad Ishfaq Ahmad; Naveed Karim; Byong-Hun Jeon; Ghulam Mustafa; Fakhar Zaman; et al. (Environmental Research, 2026)

Thiourea Mediated Improvement of Drought Stress in Maize (Zea Mays L.): Unrevealing Morpho-Physiological, Biochemical, and Root Attributes - Arslan Haider; Ejaz Ahmad Waraich; Surriya Bibi; Tahrim Ramzan; Muhammad Ahmad; Muhammad Faisal Maqsood (Journal of Soil Science and Plant Nutrition, 2026)

Mechanistic Insights into Silicon-Induced Modulation of Morphophysiological Traits and Plant Defense System in Mung Bean (Vigna Radiata L.) under Drought Stress - Mazhar Abbas; Ejaz Ahmad Waraich; Muhammad Ahmad; Nazia Ishfaq; Arslan Haider; Tahrim Ramzan; Muhammad Nazim; Usman Zulfiqar; Muhammad Faisal Maqsood; Abdul Rehman; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2026)

Enhancing Farm Productivity and Sustainability Through Maize-Soybean Intercropping with Diverse Nitrogen Management - Rukhsar Saleem; Abdul Khaliq; Muhammad Zia Ul Haq; Muhammad Aamer Maqsood (International Journal of Plant Production, 2026)

Global meta-analysis reveals nutrient-dependent symbiosis: Perennial legumes gain microbial advantages under nitrogen/phosphorus enrichment - Hai-Xia Duan; Chong-Liang Luo; Muhammad Maqsood Ur Rehman; Sheng-Rong Chen; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2026)

Health benefits of plant-based nutraceuticals: An updated review - Ahmadullah Zahir; Mustapha Muhammad Nasiru; Sammra Maqsood; Md Azizul Hakim Shiam (Food and Humanity, 2026)

Association of oral metoprolol exposure during heart failure hospitalization with death or readmission at 28-days and 6-months using a propensity score overlap-weighted EHR analysis - Azfar Athar Ishaqui; Emad Ali Alsaleh; Asaad Ahmed Asaad Khalil; Mohammed Ali Kaddoura; Khalid Orayj; Rayah Asiri; Sultan M. Alshahrani; Salman Ashfaq Ahmad; Narendar Kumar; Adnan Iqbal; Muhammad Bilal Maqsood (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Comparative disproportionality signals for methotrexate monotherapy versus methotrexate combined with hydroxychloroquine, leflunomide, or sulfasalazine in rheumatoid arthritis: newly highlighted signals evaluated using drug information safety profiles - Azfar Athar Ishaqui; Khalid Orayj; Zeeshan Ahmed; Salman Ashfaq Ahmad; Sultan M. Alshahrani; Rayah Asiri; Adnan Iqbal; Asaad Ahmed Asaad Khalil; Mohammed Ali Kaddoura; Muhammad Bilal Maqsood (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Retraction notice to ‘In-house fabrication of macro-porous biopolymeric hydrogel and its deployment for adsorptive remediation of lead and cadmium from water matrices’ [Environ. Res. 214 (2022) 113790] - Muhammad Khalid Azeem; Muhammad Rizwan; Atif Islam; Atta Rasool; Shahzad Maqsood Khan; Rafi Ullah Khan; Tahir Rasheed; Muhammad Bilal; Hafiz M.N. Iqbal (Environmental Research, 2026)

Diversity of wild Morchella (Ascomycota) revealed by integrated morphological and molecular analyses - Sania Shoukat; Nasir Mehmood; Salman Ghuffar; Sadiqa Bibi; Muhammad Rauf; Gulshan Irshad; Gule-e-Lalah Khan; Sumaira Maqsood; Tauseef Anwar; Huma Qureshi; Nazih Y. Rebouh; Salohiddinjon Yunusov; et al. (Folia Microbiologica, 2026)

AI-driven modelling and experimental analysis of oil concentration impact on mayonnaise rheology for innovative food design - Kadeejathul Kubra; Suryamol Nambyaruveettil; Malaz Suliman; Hajra Maqsood; Muhammad Waseem; Hareth Alraeesi; Arafat Husain; Mohammad Sayem Mozumder (Journal of Food Engineering, 2026)

Examining the Role of Corporate Digital Orientation in Fostering Firms’ Green Innovation: Evidence from Chinese Firm Life Cycle Stages - Murtaza Hussain; Shaohua Yang; Umer Sahil Maqsood; Muhammad Waleed Younas; R. M. Ammar Zahid (Journal of Environmental Management, 2026)

Root traits and rhizosphere responses as emerging bioindicators of microplastic pollution in agricultural soils: A review - Qudsia Saeed; Xiankai Lu; Zia Ur Rahman Farooqi; Abdul Ghafoor; Muhammad Naveed; Nimra Maqsood; Hafiz Abdul Kareem; Adnan Mustafa (Environmental Research, 2026)

Cereal-legume intercropping stabilizes yield and economic advantages under variable rainfall in semiarid rainfed environment - Wei Wang; Bao-Zhong Wang; Wei Zhang; Meng-Ying Li; Jian-Ming Li; Sheng-Jun Ji; Muhammad Abrar; Muhammad Maqsood Ur Rehman; Wasim Khan; Hong-Yan Tao; Mohamed S. Sheteiwy; Wen-Ying Wang; et al. (European Journal of Agronomy, 2026)

Potential Application of NADPH-Dependent FMN Reductase-Harboring Delftia Acidovorans in Laboratory-Scale Textile Wastewater Treatment and Re-Use - Awais Maqsood; Syeda Khola Tazeen; Sabir Hussain; Faisal Mahmood; Sher Muhammad; Muhammad Shafiq Shahid; Faizah Amer Altihani; Mohamed Hashem; Danish Riaz; Irfan Manzoor; Muhammad Shahid (Water, Air, & Soil Pollution, 2026)

Eco-Friendly Synthesis of Magnesium Oxide Nanoparticles Using Citrullus colocynthis and their Synergistic Antimicrobial Activity against Drug-Resistant Pathogens - Maqsood Qaisar; Abdul Rehman; Iffat Naz; Hassan Naveed; Baharullah Khattak; Muhammad Qasim (Current Microbiology, 2026)

Bisphenol S-induced endocrine disruption and reproductive anomalies - Benish Nawaz; Zaira Ahmad; Hanan Afzal; Kaleem Maqsood; Abdul Manan Khan; Zoya Asif; Sabahat Javed; Ali Afzal; Afzal Nimra; Muhammad Babar Khawar (Toxicology and Environmental Health Sciences, 2026)

Interface synergistic-driven electronic modulation in amorphous CoFeB@g-C3N4 for high-performance bifunctional OER/HER electrocatalysis - Abdul Haq; Anuj Kumar; Muhammad Arif; Umair Azhar; Huma Ahmad; Unaiza Talib; Mahnoor Ahmed; Muhammad Asim Mushtaq; Muhammad Sagir; Muhammad Faheem Maqsood; Kumar Venkatesan; Ghulam Yasin (Journal of Environmental Chemical Engineering, 2026)

Dissecting Microplastics Stress: Impacts of Type, Size, and Dose on Nutrient Cycling, Growth, and Antioxidant Defense System in Maize Plant - Muhammad Usman; Muhammad Zia-ur-Rehman; Muhammad Aamer Maqsood; Saddam Hussain (Water, Air, & Soil Pollution, 2026)

Effectiveness of treatments for propranolol toxicity: a systematic review of current approaches and evidence - Yafei Hu; Khizra Mujahid; Awais Ahsan; Anika Fatima; Inza; Maham Maqsood Ahmed; Maham Anoosh Butt; Sadia Younas; Muhammad Arif Aslam; Hafiz Muhammad Ahmad Javaid (European Journal of Clinical Pharmacology, 2026)

Zinc-regulated growth, chlorophyll, and antioxidant activity drive biofortification in rice varieties - Hafiza Ammara; Asma Zulfiqar; Ammara Saleem; Rehana Sardar; Usman Zulfiqar; Muhammad Aown Sammar Raza; Muhammad Faisal Maqsood; Hossam S. El-Beltagi; Mashael Daghash Alqahtani (BioMetals, 2026)

Geochemical modeling, evaluation of contaminants and impacts of land use, land cover patterns on groundwater quality in Khushab, Pakistan - Hasnain Abbas; Javed Iqbal; Syed Madhi Haider Kazmi; Maqsood Ahmed; Muhammad Ismail; Wajid Hussain (Journal of Contaminant Hydrology, 2026)

Influence of the South Pacific high on surface turbulent heat fluxes and its implications for summer heat extremes over eastern Australia - Nasir Ilyas; Muhammad Jawed Iqbal; Maqsood Alam (Acta Oceanologica Sinica, 2026)

Genome-wide identification and transcriptome-based expression analysis of hybrid sugarcane calmodulin-binding transcription activators under drought - Vitor Luciano Costa da Silva; Ana Maria Martinez; Maqsood Alam; Muhammad Noman; Antonio Chalfun-Junior (Plant Gene, 2025)

Recent progress of metallic nanomaterials in energy, biomedical and environment sector - Kinza Maqsood; Sami Ullah; Asad ur Rehman; Hafsa Bashir; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Next Research, 2025)

Double-layer stratification of Cross fluid flow with viscous dissipation and variable thermal conductivity - T. Salahuddin; A. Maqsood; Muhammad Awais; Mair Khan; Anum Tanveer; Samia Elattar (Dynamics of Atmospheres and Oceans, 2025)

Green Synthesis, Characterization, and Effect of Zinc Oxide Nanoparticles on Wheat (Triticum Aestivum L.) Under Cadmium Stress - Aqsa Khan; Samina Jam Nazeer Ahmad; Muhammad Jafir; Adeel Ahmad; Muhammad Irfan; Muhammad Qasim; Jam Nazeer Ahmad; Muhammad Azeem Sabir; Muhammad Faisal Maqsood; Abdul Rehman; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2025)

Carbon Nanotubes Improve Quantitative and Qualitative Attributes of Potato (Solanum tuberosum L) Genotypes - Muhammad Ismail; Muhammad Imtiaz; Raham Sher Khan; Fazal Jalal; Fazal Said; Muhammad Ali Khan; Syed Hussain; Badshah Islam; Salman Khan; Sabir Khan; Atta Ullah; Maqsood Khan; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Circular Economy in Oilfield Systems: A Review of Culinary Waste Materials for Sustainable Drilling Fluids - Muhammad Hammad Rasool; Syahrir Ridha; Maqsood Ahmad; Numair Ahmed Siddiqui; Muhammad Khurram Zahoor; Azam Khan; Syed Abdul Moiz Hashmi (Circular Economy and Sustainability, 2025)

Optimizing aquaculture sustainability: Microalgae-based co-culture systems for aquaculture wastewater treatment and pollution reduction - Javaeria Maqsood Gill; Syed Makhdoom Hussain; Shafaqat Ali; Ameer Fawad Zahoor; Abdulrahman Alasmari; Muhammad Munir; Eman Naeem; Muhammad Amjad; Zeeshan Yousaf; Muhammad Faisal (Algal Research, 2025)

Strategic valorization of heterogeneous organic wastes for sustainable food packaging: A circular economy approach - Shumaila Masood; Hafiz Muhammad Shahbaz; Md. Abdus Salam Shaik; Sajid Maqsood (Trends in Food Science & Technology, 2025)

Interactive effect of biochar and nano-calcium oxide on alfalfa cadmium detoxification: Boosting antioxidant defense, regulating gene expression, and remediating soil - Maqsood Ul Hussan; Sadam Hussain; Muhammad Farooq; Muhammad Habib-Ur-Rahman; Wang Jinjin; Noreen Zahra; Quanzhen Wang; Mingke Yan; Reimund P. Roetter; Kadambot H.M. Siddique (Journal of Cleaner Production, 2025)

Recent advances in conducting polymers for hybrid solar-driven evaporation systems: Fundamentals, innovations, and applications - Bushra Shakoor; Muhammad Sultan Irshad; Uzma Ghazanfar; Humaira Razzaq; Naila Arshad; Ghazala Maqsood; Iftikhar Ahmed; Muhammad Atif Ali; Muhammad Sohail Asghar; Irshad Hussain; Tao Mei; Tran Vinh Dieu; et al. (Chemical Engineering Journal, 2025)

NiMn-LDH/polypyrrole photothermal structures for interfacial solar steam generation - Ghazala Maqsood; Muhammad Sohail Asghar; Bushra Shakoor; Muneerah Alomar; Muhammad Atif Ali; Yi E; Tao Mei; Muhammad Sultan Irshad; Xianbao Wang (Chemical Engineering Journal, 2025)

Zinc-based nanoparticles improved the growth, chlorophyll, osmoregulation and ions relations of sunflower under combined shade and drought stress - Maria Tariq; Aasma Tufail; Muhammad Bilal Hafeez; Mafia Shoukat; Naeem Ahmad; Shahid Iqbal; Maqsood ul Hussan; Tayyaba Tariq; Muhammad Kamran; Muhammad Ahsan; Fahd Rasul; Noreen Zahra (Biocatalysis and Agricultural Biotechnology, 2025)

Amplification effects of AM fungus and rhizobacteria on carbon efficiency in wheat-soil system under drought stress via priming rhizosphere activities - Muhammad Maqsood Ur Rehman; Ling Zhao; Sidra Khattak; Yun-Li Xiao; Awais Iqbal; Wasim Khan; Muhammad Abrar; Zheng-Guo Cheng; Shi-Sheng Li; Asfa Batool; Ying Zhu; You-Cai Xiong (Applied Soil Ecology, 2025)

Heavy metals contamination in water, soil, and potatoes in Sargodha and Sillanwali, Pakistan, with human health implications - Kafeel Ahmad; Mutiya Zafar; Zafar Iqbal Khan; Asma Ashfaq; Muhammad Mazhar Iqbal; Tayyaba Naz; Allah Ditta; Mashal Maqsood; Shahzad Akhtar; Ijaz Rasool Noorka (Environmental Monitoring and Assessment, 2025)

Exogenic Application of Cinnamon Oil and Salicylic Acid Inhibits Alternaria Fruit Rot of Peach by Stimulating Defense-Related Enzymatic Activities - Sadia Hanif; Ambreen Maqsood; Muhammad Naveed Aslam; Muhammad Taimoor Shakeel; Atta ur Rehman; Mohammad Shafiq u Rahman; Shah Saud; Khaled Al-Kahtany; Shah Fahad (Journal of Plant Growth Regulation, 2025)

Sustainable fill solutions: recycling EPS waste in shredded EPS-clayed soil composites for improved mechanical and compaction behaviour - Muhammad Haseeb; Zain Maqsood; Muhammad Baqir; Sofia Sarwar; Badee Alshameri; Waqas Hassan; Abbas Haider; Lin Wenli; Mehtab Alam; Jiren Xie; Liu Ang; Muhammad Umar (Transportation Geotechnics, 2025)

Enhancing seismic activity classification in augmented soil gas radon time series data through computational intelligence techniques - Nadeem Bashir; Adil Aslam Mir; Muhammad Osama; Saba Maqsood Abbasi; Dimitrios Nikolopoulos; Shahzad Ahmad Qureshi; Muhammad Rafique (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Gene editing and GWAS for digital imaging analysis of wheat grain weight, size and shape are inevitable to enhance the yield - Muhammad Jamil; Waseem Ahmad; Muhammad Sanwal; Muhammad Faisal Maqsood (Cereal Research Communications, 2025)

Molecular characterization of lumpy skin disease virus in the cattle population of District Lower Chitral, Khyber Pakhtunkhwa, Pakistan - Almas Faryal Nizam; Iram Maqsood; Hanif Ur Rahman; Saira Awaz; Imran Ullah Shah; Muhammad Ijaz Ali; Baitullah Khan; Gul Muhammad; Asima Azam; Ayesha Hidayat (Antonie van Leeuwenhoek, 2025)

Functionalized carbon nanotubes interconnected with metal-organic frameworks for in-situ solar-driven evaporation and salt recovery from seawater - Muhammad Sohail Asghar; Muhammad Sultan Irshad; Naila Arshad; Maryam Al Huwayz; Muneerah Alomar; Ghazala Maqsood; Muhammad Atif Ali; Uzma Ghanzanfar; Muhammad Sabir; Jinhua Li; Van-Duong Dao; Nang Xuan Ho; et al. (Water Research, 2025)

Late Quaternary oceanographic controls on sediment distribution and transportation in the Southeast Indian Ocean; insights from IODP Site U1516 - Maqsood Ur Rahman; Tao Jiang; Muhammad Sarim; Qianru Wang; Cong Cheng (Sedimentary Geology, 2025)

Paleoceanography and marine ecosystem over 250 ky offshore Southwest Western Australia; Insight from nannofossil assemblages - Maqsood Ur Rahman; Tao Jiang; Muhammad Sarim; Qianru Wang; Muhammad Hanif; Cong Cheng (Marine Micropaleontology, 2025)

Association of microplastics with lead and cadmium in soil: Land-use and temporal trends - Noreen Khalid; Muhammad Aqeel; Shiou Yih Lee; Ujala Ejaz; Ali Noman; Muhammad Faisal Maqsood; Muhammad Kashif Irshad; Mohamed A. El-Sheikh (Journal of Environmental Chemical Engineering, 2025)

Moringa Bio-stimulator with Soil Organic Nitrogen Ameliorated Nitrogen Use Efficiency and Drought Tolerance for Healthy Proso-millet Production - Muhammad Maqsood; Nazim Hussain; Azra Yasmeen; Hamid Nawaz (Journal of Crop Health, 2025)

The Indonesian Throughflow regulated Australian summer monsoon across the Mid-Brunhes Event - Muhammad Sarim; Jian Xu; Xin Cheng; Peng Zhang; Junwen Wang; Maqsood Ur Rahman; Tayyab Jan; Hammad Ahmad (Quaternary Science Reviews, 2025)

Salicylic acid-induced defense responses against a newly identified cotton pathogen, Pantoea vagans - Muneeb Anwer; Muhammad Waqas Azam; Muhammad Taimoor Shakeel; Anam Moosa; Hongwei Zhao; Muhammad Aslam Farooqi; Mahmoud Moustafa; Mohammed O. Alshaharni; Uthman Algopishi; Huda Alghamdi; Ambreen Maqsood; Muhammad Naveed Aslam (Physiological and Molecular Plant Pathology, 2025)

Stage-dependent synergistic impacts of AM fungi and rhizobacteria on phytohormone mediation and field productivity in dryland maize - Muhammad Abrar; Ying Zhu; Wen-Shan Li; Muhammad Aqeel; Umair Ashraf; Muhammad Maqsood Ur Rehman; Jian-Ming Li; Xiao-Fang Gong; Wasim Khan; Wei Wang; You-Cai Xiong (Field Crops Research, 2025)

Alleviating cadmium-induced stress in maize: the role of zinc sulphate application on growth and biochemical responses - Sadaf Saeed; Awais Manzoor; Arslan Haider; Tahrim Ramzan; Hafeez ur Rehman; Muhammad Ahmad; Shahzad Bashir; Usman Zulfiqar; Muhammad Nazim; Muhammad Faisal Maqsood; Waleed A. A. Alsakkaf; Hayssam M. Ali (Environmental Science and Pollution Research, 2025)

MXenes: From functional innovations to solving global environmental and energy crises – A comprehensive overview and perspective - Abdul Basit; Tahir Rasheed; Haiqa Maqsood; Sana Qureshi; Shaista Zubaid; Muhammad Tuoqeer Anwar; Ali Arishi; Tauqir A. Sherazi (Journal of Environmental Chemical Engineering, 2025)

Correction: Role of ZnSO4 in Modulating Physiochemical Traits and bZIP Genes Expression in Rice Varieties Grown in Zinc-Deficient Soil - Bushra Rehman; Asma Zulfiqar; Muhammad Zafar Saleem; Maqsood Ul Hussan; Manzer H. Siddiqui; Sadam Hussain (Journal of Soil Science and Plant Nutrition, 2025)

Role of ZnSO4 in Modulating Physiochemical Traits and bZIP Genes Expression in Rice Varieties Grown in Zinc-Deficient Soil - Bushra Rehman; Asma Zulfiqar; Muhammad Zafar Saleem; Maqsood Ul Hussan; Manzer H. Siddiqui; Sadam Hussain (Journal of Soil Science and Plant Nutrition, 2025)

Biochar and Pseudomonas aeruginosa M2 Co-Application: A Sustainable Strategy for Enhancing Growth and Heavy Metal Tolerance in Brassica campestris - Muhammad Muzammil Mukhtar; Qasim Ali; Muhaimen Ayyub; Muhammad Aon; Hayssam M. Ali; Sadaf Oranab; Iftikhar Ahmad; Ghulam Abbas; Behzad Murtaza; Waqas Mohy-Ud-Din; Usman Zulfiqar; Muhammad Faisal Maqsood; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Exploring the morpho-physiological responses of maize to nickel stress modulated by salicylic acid - Atifa Masood; Sumaira Arooj; Muhammad Shahbaz; Noreen Khalid; Muhammad Sajjad; Muhammad Faisal Maqsood; Sunbal Khalil Chaudhari; Abida Abid; Rafia Zainab; Noor Fatima (Cereal Research Communications, 2025)

Geochemical and mineralogical characterization of Carboniferous-Triassic shales in Peninsular Malaysia: implications for hydrocarbon potential and depositional model - Alidu Rashid; Numair Ahmed Siddiqui; Abdul Halim Abdul Latiff; Nisar Ahmed; Maqsood Ahmad; Muhammad Jamil; Sohag Ali; Md. Mahmodul Islam (Carbonates and Evaporites, 2025)

Cereal-legume intercropping stimulates straw decomposition and promotes soil organic carbon stability - Wei Wang; Meng-Ying Li; Qing-Hui Wen; Yue Ma; Zhi-Ming Zhang; Muhammad Maqsood Ur Rehman; Fei Mo; Hong-Yan Tao; Bao-Luo Ma; Joann K. Whalen; You-Cai Xiong (Science China Life Sciences, 2025)

Application of multiple machine learning algorithms for intelligent prediction of the strength of fine-grained natural soils - Muhammad Shahroz Khalid; Zia ur Rehman; Badee Alshameri; Zain Maqsood; Fazal Hussain; Muhammad Irslan Khalid; Syed Jamal Arbi; Abbas Haider (Arabian Journal of Geosciences, 2025)

Nanoparticle-Mediated Phytohormone Interplay: Advancing Plant Resilience to Abiotic Stresses - Faizan Khalid; Yumna Rasheed; Humaira Ashraf; Kanza Asif; Muhammad Faisal Maqsood; Muhammad Shahbaz; Usman Zulfiqar; Fozia Farhat; Saher Nawaz; Muhammad Ahmad (Journal of Crop Health, 2025)

Manipulation of root-associated bacterial endophytes for sustainable crop production system: A review - Maqsood Ahmed Khaskheli; Mir Muhammad Nizamani; Entaj Tarafder; Diptosh Das; Ghulam Muhae-Ud-Din; Raheel Ahmed Khaskheli; Yong Wang (Rhizosphere, 2025)

First report of leaf spot of Wodyetia bifurcata caused by Alternaria alternata in Pakistan - Muhammad Abu Bakar; Roshaan Ahmed; Ambreen Maqsood; Muhammad Naveed Aslam; Muhammad Taimoor Shakeel (Physiological and Molecular Plant Pathology, 2025)

Fish waste biorefinery: A novel approach to promote industrial sustainability - Javaeria Maqsood Gill; Syed Makhdoom Hussain; Shafaqat Ali; Abdul Ghafoor; Muhammad Adrees; Nadia Nazish; Adan Naeem; Eman Naeem; Mohammed Ali Alshehri; Eram Rashid (Bioresource Technology, 2025)

Thymol as a Novel Plant-Derived Antibacterial Agent for Suppressing Xanthomonas citri pv. malvacearum in Cotton - Muhammad Naveed Aslam; Huma Khaliq; Hongwei Zhao; Anam Moosa; Ambreen Maqsood; Muhammad Aslam Farooqi; Muhammad Saqib Bilal; Tahir Mahmood; Tariq Mukhtar (Current Microbiology, 2025)

Straw incorporating in shallow soil layer improves field productivity by impacting soil hydrothermal conditions and maize reproductive allocation in semiarid east African Plateau - Sylvia Ngaira Indoshi; Wesly Kiprotich Cheruiyot; Muhammad Maqsood Ur Rehman; Fu-Jian Mei; Qing-Hui Wen; Alex Ndolo Munyasya; Kiprotich Koskei; David Mwehia Mburu; Aggrey Bernard Nyende; Levis Kavagi; Delphine Nyanchera Gisacho; Eliyas Feyisa Sori; et al. (Soil and Tillage Research, 2025)

Chemistry, biosynthesis, and theranostics of antioxidant flavonoids and polyphenolics of genus Rhododendron: an overview - Amjad Hussain; Sajjad Azam; Rabia Maqsood; Riaz Anwar; Muhammad Sajid Hamid Akash; Hidayat Hussain; Daijie Wang; Muhammad Imran; Katarzyna Kotwica-Mojzych; Shoaib Khan; Shabbir Hussain; Muhammad Adnan Ayub (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Diagenetic evolution of Early Eocene Chorgali Formation in the Upper Indus Basin of Pakistan: outcrop, petrographic and geochemical signatures - Muhammad Ibrar; Mumtaz Muhammad Shah; Maqsood Ur Rahman; Imran Ahmad (Carbonates and Evaporites, 2025)

Calcium oxide nanoparticles ameliorate cadmium toxicity in alfalfa seedlings by depriving its bioaccumulation, enhancing photosystem II functionality and antioxidant gene expression - Maqsood Ul Hussan; Sadam Hussain; Muhammad Adeel; Atif Ayub; Hafiz Abdul Kareem; Shaista Jabeen; Muhammad Saqib; Quanzhen Wang; Mingke Yan; Kadambot H.M. Siddique; Muhammad Tahir (Science of The Total Environment, 2024)

Long-term cereal-legume intercropping accelerates soil organic carbon loss in subsoil of dryland - Wei Wang; Guang-Rong Chen; Meng-Ying Li; Yinglong Chen; Yang Wang; Hong-Yan Tao; Hui-Zhi Hou; Muhammad Maqsood Ur Rehman; Muhammad Ashraf; Yajie Song; Levis Kavagi; Bao-Zhong Wang; et al. (Resources, Conservation and Recycling, 2024)

Molecular characterization of Peste des petits ruminants virus (PPRV) in sheep and goats and risk factors associated with it in selected districts of Khyber Pakhtunkhwa-Pakistan - Saira Awaz; Iram Maqsood; Hanif Ur Rahman; Muhammad Ijaz Ali; Baitullah Khan; Gul Muhammad; Imtiaz Ali Shah; Asima Azam; Ayesha Hidayat; Almas Faryal Nizam (Molecular Biology Reports, 2024)

CRISPR-Cas9 based molecular breeding in crop plants: a review - Muhammad Ikram; Abdul Rauf; Muhammad Junaid Rao; Muhammad Faizan Khurram Maqsood; Muhammad Zeeshan Mola Bakhsh; Maaz Ullah; Maria Batool; Muhammad Mehran; Maryam Tahira (Molecular Biology Reports, 2024)

Plant Biostimulants: Mechanisms and Applications for Enhancing Plant Resilience to Abiotic Stresses - Faizan Khalid; Yumna Rasheed; Kanza Asif; Humaira Ashraf; Muhammad Faisal Maqsood; Muhammad Shahbaz; Usman Zulfiqar; Rehana Sardar; Fasih Ullah Haider (Journal of Soil Science and Plant Nutrition, 2024)

Artificial Intelligence-Based Classification of CT Images Using a Hybrid SpinalZFNet - Faiqa Maqsood; Wang Zhenfei; Muhammad Mumtaz Ali; Baozhi Qiu; Naveed Ur Rehman; Fahad Sabah; Tahir Mahmood; Irfanud Din; Raheem Sarwar (Interdisciplinary Sciences: Computational Life Sciences, 2024)
The kidney is an abdominal organ in the human body that supports filtering excess water and waste from the blood. Kidney diseases generally occur due to changes in certain supplements, medical conditions, obesity, and diet, which causes kidney function and ultimately leads to complications such as chronic kidney disease, kidney failure, and other renal disorders. Combining patient metadata with computed tomography (CT) images is essential to accurately and timely diagnosing such complications. Deep Neural Networks (DNNs) have transformed medical fields by providing high accuracy in complex tasks. However, the high computational cost of these models is a significant challenge, particularly in real-time applications. This paper proposed SpinalZFNet, a hybrid deep learning approach that integrates the architectural strengths of Spinal Network (SpinalNet) with the feature extraction capabilities of Zeiler and Fergus Network (ZFNet) to classify kidney disease accurately using CT images. This unique combination enhanced feature analysis, significantly improving classification accuracy while reducing the computational overhead. At first, the acquired CT images are pre-processed using a median filter, and the pre-processed image is segmented using Efficient Neural Network (ENet). Later, the images are augmented, and different features are extracted from the augmented CT images. The extracted features finally classify the kidney disease into normal, tumor, cyst, and stone using the proposed SpinalZFNet model. The SpinalZFNet outperformed other models, with 99.9% sensitivity, 99.5% specificity, precision 99.6%, 99.8% accuracy, and 99.7% F1-Score in classifying kidney disease. Graphical Abstract

Efficacy and safety of ticagrelor monotherapy following a brief DAPT vs. prolonged 12-month DAPT in ACS patients post-PCI: a meta-analysis of RCTs - Usama Qamar; Farhan Naeem; Muhammad Talha Maqsood; Maleeka Zamurad Khan; Zeeshan Imtiaz; Fatima Saeed; Neelesh Gupta; Fnu Zafarullah Brohi; Celestine Mkpozi; Yasar Sattar (European Journal of Clinical Pharmacology, 2024)

Optimal substitution of inorganic fertilizer with organic amendment sustains rainfed maize production and decreases soil N2O emissions by modifying denitrifying bacterial communities in Northern China - Lihua Xie; Lingling Li; Junhong Xie; Jinbin Wang; Muhammad Zahid Mumtaz; Zechariah Effah; Setor Kwami Fudjoe; Maqsood Ahmed Khaskheli; Zhuzhu Luo; Linzhi Li (European Journal of Agronomy, 2024)

Resilient mechanism of strigolactone (GR24) in regulating morphological and biochemical status of maize under salt stress - Iqra Iftikhar; Muhammad Shahbaz; Muhammad Faisal Maqsood; Usman Zulfiqar; Shamsa Rana; Fozia Farhat; Hira Farooq; Kamran Ahmad; Muhammad Jamil; Fasih Ullah Haider; Saltanat Aghayeva (Biocatalysis and Agricultural Biotechnology, 2024)

Nano-Selenium: A Green Promising Approach against Abiotic Stresses in Plants - Mariam Fatima; Asia Maqbool; Rehana Sardar; Muhammad Faisal Maqsood; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2024)

Effects of Withania somnifera (L.) Dunal in acute pulmonary pathophysiology in a rat model of smoke-induced lung injury and role of IRS-1 and SOX-2 - Sana Saleem; Imran Mukhtar; Hanan Y. Aati; Humaira Muzaffar; Haseeb Anwar; Musaddique Hussain; Maqsood Ahmad; Muhammad Umair; Kashif-ur-Rehman Khan (South African Journal of Botany, 2024)

Comprehensive chemical profiling with UHPLC-MS, in-vitro, in-silico, and in-vivo antidiabetic potential of Typha domingensis Pers; A novel source of bioactive compounds - Rizwana Dilshad; Kashif-ur-Rehman Khan; Rihana Dilshad; Saeed Ahmad; Huma Rao; Umair Khurshid; Sultan Ahmad; Maqsood Ahmad; Hafiz Muhammad Usman Abid; Muhammad Kashif Zaman; Rabia Nisar; Saharish Khaliq; et al. (South African Journal of Botany, 2024)

Ypresian–Lutetian platform evolution in the Indus Basin, Southwestern Pakistan: An interplay between local and regional tectonic changes - Maqsood Ur Rahman; Muhammad Hanif; Tao Jiang; Wang Qianru; Fulong Ning; Muhammad Sarim; Muhammad Rizwan; Faheem Ahmed (Sedimentary Geology, 2024)

A novel computational methodology to design solar radiation absorbing glass - Faraan Fareed; Uzma Habib; Hafiz Ali Haider Sehole; Salma Sherbaz; Muhammad Bilal Khan Niazi; Adnan Maqsood (Energy and Buildings, 2024)

Extremophiles and their enzymatic diversity and biotechnological potential - Fatima Atif; Nida Maqsood; Wajeeha Ali; Wajid Ali; Muhammad Irfan (Systems Microbiology and Biomanufacturing, 2024)

Endophytic Bacillus spp. Mediated Plant Growth Promotion of Tomato Seedlings and Suppression of Meloidogyne incognita and Fusarium oxysporum Disease Complex - Ambreen Maqsood; Muhammad Naveed Aslam; Huma Khaliq; Muhammad Taimoor Shakeel; Haiyan Wu; Shah Fahad (Journal of Plant Growth Regulation, 2024)

Enhancing Plant Stress Resilience with Osmolytes and Nanoparticles - Yumna Rasheed; Faizan Khalid; Humaira Ashraf; Kanza Asif; Muhammad Faisal Maqsood; Nargis Naz; Muhammad Shahbaz; Usman Zulfiqar; Qasim Ali; Shamsa Rana (Journal of Soil Science and Plant Nutrition, 2024)

Salicylic Acid-Induced Antioxidant Defense System Alleviates Cadmium Toxicity in Wheat - Umer Hayat; Kaleem ul din; Arslan Haider; Tahrim Ramzan; Bilal Ahmad Shahzad; Muhammad Ahmad; Usman Zulfiqar; Muhammad Faisal Maqsood; Sadam Hussain; Mona S. Alwahibi; Mohamed S. Elshikh (Journal of Soil Science and Plant Nutrition, 2024)

Soil Organic Carbon and Nitrogen Mineralization Potential of Manures Regulated by Soil Microbial Activities in Contrasting Soil Textures - Waqar Ahmed; Muhammad Nadeem Ashraf; Muhammad Sanaullah; Muhammad Aamir Maqsood; Muhammad Ahmed Waqas; Shafeeq Ur Rahman; Saddam Hussain; Hammad Raza Ahmad; Adnan Mustafa; Xu Minggang (Journal of Soil Science and Plant Nutrition, 2024)

Correction: A detailed investigation of Jutana formation for depositional setting in Indus Basin, Pakistan - Muhammad Ibrar; Hameed Ur Rehman; Suleman Khan; Syed Saddam Hussain; Maqsood Ur Rahman; Abdullah Khan (Carbonates and Evaporites, 2024)

A detailed investigation of Jutana Formation for depositional setting in Indus Basin, Pakistan - Muhammad Ibrar; Hameed Ur Rehman; Suleman Khan; Syed Saddam Hussain; Maqsood Ur Rahman; Abdullah Khan (Carbonates and Evaporites, 2024)

Deforestation detection and reforestation potential due to natural disasters—A case study of floods - Muhammad Hassan Maqsood; Rafia Mumtaz; Muhammad Ajmal Khan (Remote Sensing Applications: Society and Environment, 2024)

Genetic biofortification: advancing crop nutrition to tackle hidden hunger - Usman Zulfiqar; Amman Khokhar; Muhammad Faisal Maqsood; Muhammad Shahbaz; Nargis Naz; Maheen Sara; Sana Maqsood; Sajila Sahar; Saddam Hussain; Muhammad Ahmad (Functional & Integrative Genomics, 2024)

Retraction Note: Asymmetric effect of FDI and public expenditure on population health: new evidence from Pakistan based on non-linear ARDL - Saif ur Rahman; Imran Sharif Chaudhry; Muhammad Saeed Meo; Salman Maqsood Sheikh; Sadia Idrees (Environmental Science and Pollution Research, 2024)

Above-and below-ground feedback loop of maize is jointly enhanced by plant growth-promoting rhizobacteria and arbuscular mycorrhizal fungi in drier soil - Wasim Khan; Ying Zhu; Aziz Khan; Ling Zhao; Yu-Miao Yang; Ning Wang; Meng Hao; Yue Ma; Jaya Nepal; Fazal Ullah; Muhammad Maqsood Ur Rehman; Muhammad Abrar; et al. (Science of The Total Environment, 2024)

Progress in layered double hydroxides (LDHs): Synthesis and application in adsorption, catalysis and photoreduction - Ahmad Farhan; Aman Khalid; Nimra Maqsood; Sidra Iftekhar; Hafiz Muhammad Adeel Sharif; Fei Qi; Mika Sillanpää; Muhammad Bilal Asif (Science of The Total Environment, 2024)

Chitosan nanoparticles encapsulating curcumin counteract salt-mediated ionic toxicity in wheat seedlings: an ecofriendly and sustainable approach - Arruje Hameed; Waqas Maqsood; Amjad Hameed; Muhammad Abdul Qayyum; Toheed Ahmed; Tahir Farooq (Environmental Science and Pollution Research, 2024)

Patterns of bacterial communities in the rhizosphere and rhizoplane of alpine wet meadows - Awais Iqbal; Muhammad Maqsood Ur Rehman; Wasim Sajjad; Abraham Allan Degen; Muhammad Rafiq; Niu Jiahuan; Salman Khan; Zhanhuan Shang (Environmental Research, 2024)

Yield loss of inferior crop species and its physiological mechanism in a semiarid cereal-legume intercropping system - Wei Wang; Jian-Hua Zhao; Meng-Ying Li; Wei Zhang; Muhammad Maqsood Ur Rehman; Bao-Zhong Wang; Fazal Ullah; Zheng-Guo Cheng; Li Zhu; Jin-Lin Zhang; Hong-Yan Tao; Wen-Ying Wang; et al. (European Journal of Agronomy, 2024)

Green synthesized silver nanoparticles: Characterization, phytostimulatory impacts, and degradation potential for organic pollutants - Ghania Abbas; Fozia Batool; Ambreen Ahmed; Shabana Wagi; Humaira Yasmeen Gondal; Farah Maqsood; Ehab A. Abdelrahman; Hafiza Komal Naeem; Samia Kanwal; Muhammad Mustaqeem; Allah Ditta (Biocatalysis and Agricultural Biotechnology, 2024)

Hydrogeochemistry and prediction of arsenic contamination in groundwater of Vehari, Pakistan: comparison of artificial neural network, random forest and logistic regression models - Javed Iqbal; Chunli Su; Maqsood Ahmad; Muhammad Yousuf Jat Baloch; Abdur Rashid; Zahid Ullah; Hasnain Abbas; Anam Nigar; Asmat Ali; Arif Ullah (Environmental Geochemistry and Health, 2024)

Plant-based foods and hepatocellular carcinoma: A review on mechanistic understanding - Raakia Anam Saeed; Maria Maqsood; Raafia Anam Saeed; Hafiz Shehzad Muzammil; Muhammad Issa Khan; Laiba Asghar; Sahar Un Nisa; Roshina Rabail; Rana Muhammad Aadil (Critical Reviews in Food Science and Nutrition, 2023)

An Integrated Approach for Biodegradation of Toxic Azo Dyes and Wastewater Recycling by Azoreductase Gene–Harboring Bacillus paramycoides Strain AM-3 - Awais Maqsood; Khola Tazeen; Sabir Hussain; Faisal Mahmood; Muhammad Shahid (Water, Air, & Soil Pollution, 2023)

Correction to: Genetic modification strategies for enhancing plant resilience to abiotic stresses in the context of climate change - Amman Khokhar; Muhammad Shahbaz; Muhammad Faisal Maqsood; Usman Zulfiqar; Nargis Naz; Usama Zafar Iqbal; Maheen Sara; Muhammad Aqeel; Noreen Khalid; Ali Noman; Faisal Zulfiqar; Khalid M. Al Syaad; et al. (Functional & Integrative Genomics, 2023)

Solubilization and Uptake of Phosphorus (P) by Wheat and Maize Crops from Indigenous Rock Phosphate Applied with Biogas Slurry and Bagasse Ash - Ammara Farooq; Bushra Saeed; Hafiz Muhammad Bilal; Muhammad Aamer Maqsood; Muhammad Nasim; Tariq Aziz; Minggang Xu (Water, Air, & Soil Pollution, 2023)

Adsorption potential of orange rind–based nanosorbents for the removal of cadmium(II) and chromium(VI) from contaminated water - Samia Kanwal; Hafiza Komal Naeem; Fozia Batool; Awais Mirza; Ehab A. Abdelrahman; Gulnaz Sharif; Farah Maqsood; Muhammad Mustaqeem; Allah Ditta (Environmental Science and Pollution Research, 2023)

Cotton and drought stress: An updated overview for improving stress tolerance - Sadia Zafar; Hadiqa Afzal; Areeba Ijaz; Athar Mahmood; Atif Ayub; Airish Nayab; Sadam Hussain; Maqsood UL-Hussan; Muhammad Azeem Sabir; Usman Zulfiqar; Faisal Zulfiqar; Anam Moosa (South African Journal of Botany, 2023)

Nano priming for boosting growth and resilience in crops under abiotic stresses - Faizan Khalid; Kanza Asif; Yumna Rasheed; Humaira Ashraf; Muhammad Faisal Maqsood; Shamsa Rana; Usman Zulfiqar; Nargis Naz; Muhammad Shahbaz; Rehana Sardar; Zunaira Riaz (Biocatalysis and Agricultural Biotechnology, 2023)

Exogenous Application of Moringa Leaf Extract Confers Salinity Tolerance in Sunflower by Concerted Regulation of Antioxidants and Secondary Metabolites - Fozia Farhat; Nadra Ashaq; Ali Noman; Muhammad Aqeel; Shameem Raja; Rashda Naheed; Muhammad Faisal Maqsood; Ijaz Haider; Arneeb Tariq (Journal of Soil Science and Plant Nutrition, 2023)

Role of Exogenous Osmolyte Supplementation in Ameliorating Osmotic and Oxidative Stress and Promoting Growth in Salinity-Stressed Soybean Genotypes - Muhammad Anwar-ul-Haq; Irfan Iftikhar; Javaid Akhtar; Muhammad Maqsood (Journal of Soil Science and Plant Nutrition, 2023)

Genetic modification strategies for enhancing plant resilience to abiotic stresses in the context of climate change - Amman KhokharVoytas; Muhammad Shahbaz; Muhammad Faisal Maqsood; Usman Zulfiqar; Nargis Naz; Usama Zafar Iqbal; Maheen Sara; Muhammad Aqeel; Noreen Khalid; Ali Noman; Faisal Zulfiqar; Khalid M. Al Syaad; et al. (Functional & Integrative Genomics, 2023)

Correction to: Molecular and genetic insights into secondary metabolic regulation underlying insect‑pest resistance in legumes - Muhammad Khuram Razzaq; Aiman Hina; Asim Abbasi; Benjamin Karikari; Hafiza Javaria Ashraf; Muhammad Mohiuddin; Sumaira Maqsood; Aqsa Maqsood; Inzamam Ul Haq; Guangnan Xing; Ghulam Raza; Javaid Akhter Bhat (Functional & Integrative Genomics, 2023)

Molecular and genetic insights into secondary metabolic regulation underlying insect-pest resistance in legumes - Muhammad Khuram Razzaq; Aiman Hina; Asim Abbasi; Benjamin Karikari; Hafiza Javaria Ashraf; Muhammad Mohiuddin; Sumaira Maqsood; Aqsa Maqsood; Inzamam Ul Haq; Guangnan Xing; Ghulam Raza; Javaid Akhter Bhat (Functional & Integrative Genomics, 2023)

Correction: KASP mapping of QTLs for yield components using a RIL population in Basmati rice (Oryza sativa L.) - Hamza Ashfaq; Reena Rani; Naila Perveen; Allah Ditta Babar; Umer Maqsood; Muhammad Asif; Katherine A. Steele; Muhammad Arif (Euphytica, 2023)

Diurnal variation in the atmospheric electric field with respect to aerosol and meteorological parameters at Islamabad, Pakistan - Samia Faiz Gurmani; Nabeel Ahmad; Tabinda Shamsher; Tariq Mehmood; Waqas Khalid; Asghari Maqsood; Talat Iqbal; Muhammad Ali Shah (Journal of Earth System Science, 2023)

Hydrogen Peroxide Promotes Terminal Heat Stress Recovery in Wheat by Strengthening Leaf Physiological Functioning - Muhammad Sarwar; Muhammad Farrukh Saleem; Siraj Ahmed; Hamza Maqsood; Saddam Hussain; Muhammad Ashfaq Wahid; Muhammad Kashif Munir; Muhammad Zafar; Najeeb Ullah; Ali Khoddami (Journal of Plant Growth Regulation, 2023)

KASP mapping of QTLs for yield components using a RIL population in Basmati rice (Oryza sativa L.) - Hamza Ashfaq; Reena Rani; Naila Perveen; Allah Ditta Babar; Umer Maqsood; Muhammad Asif; Katherine A. Steele; Muhammad Arif (Euphytica, 2023)
Super Basmati is an elite variety with extra-long grains and superior quality but its yield is severely affected by water stress. Recombinant inbred lines (RILs) developed from the cross of Super Basmati and IR55419-04 (a coarse grained variety with high yield potential) were used to identify and map yield-related quantitative trait loci (QTLs) under normal field conditions. Genotypes for 244 KASP markers were obtained from 188 F 9 RILs and a linkage map constructed of 1369.4 cM, with average marker interval of 10.5 cM. Eleven agronomic traits were phenotyped in RILs and parents. Composite interval mapping and inclusive composite interval mapping model identified 21 common QTLs related to nine agronomic traits; of the QTLs identified, twelve mapped at novel positions. LOD scores ranged from 2.51 for number of filled grains ( qFG1.1 ) to 16.8 for plant height ( qPH1.1 ). Four major effect QTLs could explain 20% of variation related for plant height, hundred-grain weight and grain width. Alleles from IR55419-04 improved grain filling, grain weight and grain width, while alleles from Super Basmati contributed to longer grains, panicles and flag leaves. Putative candidate genes were identified for 18 yield-related QTLs. These results validate the use of KASP genotyping for QTL mapping of yield-related traits in a bi-parental segregating population. SNPs in the QTLs identified in this study can be used in marker assisted selection for yield components to improve Basmati rice.

Zinc oxide nanoparticles coated urea enhances nitrogen efficiency and zinc bioavailability in wheat in alkaline calcareous soils - Shaiza Amin; Tariq Aziz; Muhammad Zia-ur-Rehman; Ifra Saleem; Muhammad Rizwan; Ambreen Ashar; Hafiz Adnan Mussawar; Muhammad Aamer Maqsood (Environmental Science and Pollution Research, 2023)

First report of leaf spot of Aloe vera caused by Curvularia spicifera in Pakistan - Roshaan Ahmed; Muhammad Naveed Aslam; Anam Moosa; Muhammad Taimoor Shakeel; Ambreen Maqsood (Journal of Plant Pathology, 2023)

Green metal oxides coated biochar nanocomposites preparation and its utilization in vertical flow constructed wetlands for reactive dye removal: Performance and kinetics studies - Ruba Munir; Khuram Ali; Syed Abbas Zilqurnain Naqvi; Amna Muneer; Muhammad Zeeshan Bashir; Muhammad Aamer Maqsood; Saima Noreen (Journal of Contaminant Hydrology, 2023)

Expression of pro-inflammatory cytokines (IL-6 & IL-18) exacerbate the risk of diabetic nephropathy in the Pakistani population - Maha Maqsood; Saima Sharif; Shagufta Naz; Tasnim Farasat; Farkhanda Manzoor; Maqsood Cheema; Muhammad Saqib (Molecular Biology Reports, 2023)

Late Pleistocene chronostratigraphy and biostratigraphy of Mentelle Basin and its implications for global correlation - Maqsood Ur Rahman; Tao Jiang; Muhammad Sarim; Muhammad Hanif; Timothy T. Barrows; Yipan Hu (Marine Geology, 2023)

Manipulation of plant growth stimulants on plant morphology, phenology, and disease incident of Gossypium hirsutum L. under various thermal regimes - Muhammad Sarwar; Muhammad Farrukh Saleem; Basharat Ali; Muhammad Sagir; Muhammad Bilal Tahir; Muhammad Ashfaq Wahid; Muhammad Shahid; Theodore M. Mwamba; Bilal Ahmad Khan; Hamza Maqsood (Arabian Journal of Geosciences, 2023)

Late quaternary clay mineral and grain-size records from northwest Australia and their implications for paleoclimate, ocean currents, and paleodrainage of the Bonaparte basin - Muhammad Sarim; Jian Xu; Peng Zhang; Maqsood Ur Rahman; Benazeer Iqbal; Jianghua Qiao; Fei Ke; Yazhou Ran (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Comparative Assessment of Remediation Potential of Xanthium strumarium Ecotypes in NaCl-Affected Root Zone - Noreen Akhter; Muhammad Aqeel; Muhammad Faisal Maqsood; Saher Nawaz; Muhammad Muslim Shahnaz; Noreen Khalid; Mohammed A. Basahi; Omar Mahmoud Al-Zoubi; Talaat Habeeb; Romina Alina Marc; Muhammad Kashif Irshad; Ali Noman (Water, Air, & Soil Pollution, 2022)

Diversity among synthetic backcross-derived wheat (Triticum aestivum L.) lines for drought tolerance - Muhammad Sohail; Maqsood Qamar; Imtiaz Hussain (Euphytica, 2022)

Mediation of Growth and Metabolism of Pisum sativum in Salt Stress Potentially Be Credited to Thiamine - Rashda Naheed; Maryeum Zahid; Muhammad Aqeel; Muhammad Faisal Maqsood; Hina Kanwal; Noreen Khalid; Mohamed Hashem; Saad Alamri; Ali Noman (Journal of Soil Science and Plant Nutrition, 2022)

Pcal_2031, a RecA/Rad51 homologue from Pyrobaculum calidifontis, complements the ultraviolet light sensitivity of Escherichia coli - Syed Nasim Abbas; Mehwish Aslam; Amina Maqsood; Hafiza Zumra Fatima; Muhammad Arshad Javed; Naeem Rashid (Biologia, 2022)

Moisture- and period-dependent interactive effects of plant growth-promoting rhizobacteria and AM fungus on water use and yield formation in dryland wheat - Muhammad Maqsood Ur Rehman; Ying Zhu; Muhammad Abrar; Wasim Khan; Wei Wang; Awais Iqbal; Anum Khan; Yuan Chen; Muhammad Rafiq; Muhammad Aammar Tufail; Jian-Sheng Ye; You-Cai Xiong (Plant and Soil, 2022)

Development of Organically Complexed-Bioaugmented Boron-Coated DAP and Its Effect on Yield and Quality of Canola (Brassica napus L.) - Tayyaba Samreen; Muhammad Imran; Zahir Ahmad Zahir; Muhammad Zulqernain Nazir; Saima Noureen; Safdar Bashir; Sehrish Kanwal; Hassan Munir; Muhammad Aamer Maqsood (Journal of Plant Growth Regulation, 2022)

Apportionment of heavy metals in a soil–water-plant system via brick kiln emissions in heavily industrialized city of Pakistan - Imran Ahmad; Hamaad Raza Ahmad; Zia Ur Rahman Farooqi; Muhammad Sabir; Muhammad Rizwan; Muhammad Aamer Maqsood (Environmental Science and Pollution Research, 2022)

Novel strategies and advancement in reducing heavy metals from the contaminated environment - Quratulain Maqsood; Nazim Hussain; Mehvish Mumtaz; Muhammad Bilal; Hafiz M. N. Iqbal (Archives of Microbiology, 2022)

Interactive effect of amino acids balanced at ideal lysine ratio and exogenous protease supplemented to low CP diet on growth performance, carcass traits, gut morphology, and serum metabolites in broiler chicken - Muhammad Adeel Maqsood; Ehsaan Ullah Khan; Shafqat Nawaz Qaisrani; Muhammad Afzal Rashid; Muhammad Shabir Shaheen; Azhar Nazir; Hammad Talib; Sohail Ahmad (Tropical Animal Health and Production, 2022)

Comparative Effect of Various Organic Extracts Coated Urea Fertilizer on the Release Pattern of Ammonium and Nitrate in the Soil at Different Time Intervals - Adeel Ahmad; Muhammad Yaseen; Hafiz Naeem Asghar; Shahzad Maqsood Ahmed Basra (Journal of Soil Science and Plant Nutrition, 2022)

Ameliorative Effect of Silicic Acid and Silicates on Oxidative, Osmotic Stress, and Specific Ion Toxicity in Spring Wheat (Triticum aestivum L.) Genotypes - Muhammad Nadeem; Muhammad Anwar-ul-Haq; Muhammad Saqib; Muhammad Maqsood; Zhenli He (Journal of Soil Science and Plant Nutrition, 2022)

Choline Chloride Mediates Chromium Tolerance in Spinach (Spinacia oleracea L.) by Restricting its Uptake in Relation to Morpho-physio-biochemical Attributes - Iqbal Hussain; Muhammad Hamzah Saleem; Sahar Mumtaz; Rizwan Rasheed; Muhammad Arslan Ashraf; Faisal Maqsood; Muzammal Rehman; Humaira Yasmin; Shakeel Ahmed; Muhammad Ishtiaq; Sana Anwar; Shafaqat Ali (Journal of Plant Growth Regulation, 2022)

The Interactive Approach of Rhizobacteria and l-tryptophan on Growth, Physiology, Tuber Characteristics, and Iron Concentration of Potato (Solanum tuberosum L.) - Zain Mushtaq; Hafiz Naeem Asghar; Zahir Ahmad Zahir; Muhammad Maqsood (Journal of Plant Growth Regulation, 2022)

Development of Basmati lines by the introgression of three bacterial blight resistant genes through marker-assisted breeding - Allah Ditta Babar; Abha Zaka; Shahzad Amir Naveed; Niaz Ahmad; Kashif Aslam; Muhammad Asif; Umer Maqsood; Casiana M. Vera Cruz; Muhammad Arif (Euphytica, 2022)

Reducing nutrient uptake in okra weeds by suppressing their population through alligator weed compost mulch for better pod yield and quality - Asif Tanveer; Muhammad Sarwar; Muhammad Shahbaz Asghar; Muhammad Farrukh Saleem; Hamza Maqsood; Basharat Ali; Muhammad Kashif Munir; Muhammad Arshad; Rao Muhammad Ikram; Nabeel Ahmad Ikram; Muhammad Rizwan (Arabian Journal of Geosciences, 2022)

Effects of mirror and coloured balls as environmental enrichment tools on performance, welfare and meat quality traits of commercial broiler - Muhammad Shahid Zahoor; Sohail Ahmad; Muhammad Usman; Muhammad Dawood; Karim El-Sabrout; Syed Ghulam Mohayud Din Hashmi; Ehsaan Ullah Khan; Murrawat Hussain; Muhammad Adeel Maqsood; Hafiz Rao Abdul Latif (Tropical Animal Health and Production, 2022)

RETRACTED ARTICLE: Asymmetric effect of FDI and public expenditure on population health: new evidence from Pakistan based on non-linear ARDL - Saif ur Rahman; Imran Sharif Chaudhry; Muhammad Saeed Meo; Salman Maqsood Sheikh; Sadia Idrees (Environmental Science and Pollution Research, 2022)

Cadmium Toxicity in Plants: Recent Progress on Morpho-physiological Effects and Remediation Strategies - Usman Zulfiqar; Aqsa Ayub; Saddam Hussain; Ejaz Ahmad Waraich; Mohamed A. El-Esawi; Muhammad Ishfaq; Muhammad Ahmad; Nauman Ali; Muhammad Faisal Maqsood (Journal of Soil Science and Plant Nutrition, 2022)

Quantitative evaluation of zinc metal in meadows and ruminants for health assessment: implications for humans﻿ - Ayesha Maqsood; Zafar Iqbal Khan; Kafeel Ahmad; Shahzad Akhtar; Asma Ashfaq; Ifra Saleem Malik; Razia Sultana; Muhammad Nadeem; Jawaher Alkahtani; Yheni Dwiningsih; Mohamed S. Elshikh (Environmental Science and Pollution Research, 2022)

Insect pests of economic importance attacking wheat crop (Triticum aestivum L.) in Punjab, Pakistan - Dilbar Hussain; Muhammad Asrar; Bushra Khalid; Faisal Hafeez; Muhammad Saleem; Muazzma Akhter; Maqsood Ahmed; Imran Ali; Kanwal Hanif (International Journal of Tropical Insect Science, 2022)

Chromium (VI)-Induced Leaf-Based Differential Physiological, Metabolic and Microstructural Changes in Two Transgenic Cotton Cultivars (J208, Z905) and Their Hybrid Line (ZD14) - M. K. Daud; Shafaqat Ali; M. T. Variath; Mumtaz Khan; Muhammad Jamil; Maqsood Ahmad; S. J. Zhu (Journal of Plant Growth Regulation, 2022)

Ecological risk assessment of heavy metal chromium in a contaminated pastureland area in the Central Punjab, Pakistan: soils vs plants vs ruminants - Fu Chen; Fatima Ghulam Muhammad; Zafar Iqbal Khan; Kafeel Ahmad; Muhammad Nadeem; Shahid Mahmood; Muhammad Umar Farooq Awan; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Ayesha Maqsood; et al. (Environmental Science and Pollution Research, 2022)

Evaluation of potential ecological risk and prediction of zinc accumulation and its transfer in soil plants and ruminants: public health implications - Fu Chen; Laraib Saqlain; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Asma Ashfaq; Razia Sultana; Fatima Ghulam Muhammad; Ayesha Maqsood; Majida Naeem; Ifra Saleem Malik; Mudasra Munir; et al. (Environmental Science and Pollution Research, 2022)

Correction to: First report of Alternaria alternata causing post‑harvest brown spot of Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Muhammad Naveed Aslam; Tanvir Ahmad; Ambreen Maqsood; Muhammad Shafique (Journal of Plant Pathology, 2021)

First report of Alternaria alternata causing post-harvest brown spot of Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Muhammad Naveed Aslam; Tanvir Ahmad; Ambreen Maqsood; Muhammad Shafique (Journal of Plant Pathology, 2021)

Strigolactone (GR24) Induced Salinity Tolerance in Sunflower (Helianthus annuus L.) by Ameliorating Morpho-Physiological and Biochemical Attributes Under In Vitro Conditions - Hira Zulfiqar; Muhammad Shahbaz; Muhammad Ahsan; Muhammad Nafees; Hammad Nadeem; Muhammad Akram; Ambreen Maqsood; Sunny Ahmar; Muhammad Kamran; Saud Alamri; Manzer H. Siddiqui; Shah Saud; et al. (Journal of Plant Growth Regulation, 2021)

Agricultural water management challenges in the Hunza River Basin: Is a solar water pump an alternative option?* - Madhav Prasad Dhakal; Amjad Ali; Muhammad Zafar Khan; Nisha Wagle; Ghulam Muhammad Shah; Muhammad Mudassar Maqsood; Ajaz Ali (Irrigation and Drainage, 2021)
In the glaciated mountains of the Upper Indus Basin of Pakistan, glacier‐ and snowmelt‐ based irrigation systems have been established over several centuries to secure water for cultivation. However, these systems are now facing several challenges, being sensitive to climate change and thus exposed to the resulting extreme events such as glacial lake outburst floods (GLOFs) and flash floods, also difficult terrain and access paths, male outmigration, limited technical capacity and a weak policy and governance system. Hence, exploring the potential options for overcoming the challenges and irrigating arable barren land could lead to economic prosperity and environmental gains. A literature review, stakeholder consultation and semi‐structured questionnaire survey in two villages of the Hunza River basin was conducted to synthesize information in different domains. Information on the irrigation system and its sources, water distribution/allocation system, challenges and adaptation strategies were collected, and based on community preferences, an alternative irrigation technological package was established to overcome the challenges and irrigate barren land. A customized solar water lifting pump with an efficient micro‐irrigation package was piloted which proved to be climate resilient. The system is simple to adopt, uses clean energy for operation and is economically feasible, with a benefit–cost ratio of 4.96 and a payback period of around 11 years.

Expression profiling of miRNA-196a biomarker in naïve hepatitis C virus-infected and Sofosbuvir plus Daclatasvir-treated patients - Nazim Hussain; Nimrah Farooq; Muhammad Maqsood; Muhammad Shahid Riaz Rajoka; Muhammad Bilal (Archives of Microbiology, 2021)

Genetic and expression deregulation of immunoregulatory genes in rheumatoid arthritis - Muhammad Zhaid Hussain; Ishrat Mahjabeen; Muhammad Shahid Khan; Naila Mumtaz; Syed Uzair Maqsood; Farooq Ikram; Syed Nazir Ahmed; Qurrat-ul-Ain Kalim; Rabia Abbas; Ahmed Ammar Cheema (Molecular Biology Reports, 2021)

Effect of feeding calcium propionate supplemented cotton seed cake on milk yield, milk composition and aflatoxin concentration in lactating buffaloes - Murtaza Ali Tipu; Anjum Khalique; Muhammad Naveed-ul-Haque; Muhammad Qamer Shahid; Maqsood Akhtar; Mubashir Ilyas (Tropical Animal Health and Production, 2021)

Microfacies analysis and depositional environments of the Upper Cretaceous Fort Munro Formation in the Rakhi Nala Section, Sulaiman range, Pakistan - Muhammad Rizwan; Muhammad Hanif; Nowrad Ali; Maqsood Ur Rehman (Carbonates and Evaporites, 2020)

Characterizing Lentil Germplasm for Zinc Biofortification and High Grain Output - Naser Rasheed; Muhammad Aamer Maqsood; Tariq Aziz; Abdul Jabbar (Journal of Soil Science and Plant Nutrition, 2020)

Iron Nutrition Improves Productivity, Profitability, and Biofortification of Bread Wheat under Conventional and Conservation Tillage Systems - Usman Zulfiqar; Muhammad Maqsood; Saddam Hussain; Muhammad Anwar-ul-Haq (Journal of Soil Science and Plant Nutrition, 2020)

The engineering assessments and potential aggregate analysis of mesozoic carbonates of Kohat Hills Range, KP, Pakistan - Gohar Rehman; Guangcheng Zhang; Maqsood Ur Rahman; Naveed Ur Rahman; Tariq Usman; Muhammad Imraz (Acta Geodaetica et Geophysica, 2020)

Achromobacter sp. FB-14 harboring ACC deaminase activity augmented rice growth by upregulating the expression of stress-responsive CIPK genes under salinity stress - Muhammad Shahid; Asad Ali Shah; Farwa Basit; Muhammad Noman; Muhammad Zubair; Temoor Ahmed; Tahir Naqqash; Irfan Manzoor; Awais Maqsood (Brazilian Journal of Microbiology, 2020)

Nanocarrier-mediated co-delivery systems for lung cancer therapy: recent developments and prospects - Muhammad Asim Farooq; Md Aquib; Daulat Haleem Khan; Sana Ghayas; Anam Ahsan; Muhammad Ijaz; Parikshit Banerjee; Maqsood Ahmed Khan; Muhammad Masood Ahmad; Bo Wang (Environmental Chemistry Letters, 2019)

iNuc-ext-PseTNC: an efficient ensemble model for identification of nucleosome positioning by extending the concept of Chou’s PseAAC to pseudo-tri-nucleotide composition - Muhammad Tahir; Maqsood Hayat; Sher Afzal Khan (Molecular Genetics and Genomics, 2019)

Sugar beet extract acts as a natural bio-stimulant for physio-biochemical attributes in water stressed wheat (Triticum aestivum L.) - Ali Noman; Qasim Ali; Jazia Naseem; M. Tariq Javed; Hina Kanwal; Waqar Islam; Muhammad Aqeel; Noreen Khalid; Sara Zafar; Muhammad Tayyeb; Naeem Iqbal; Mahmooda Buriro; et al. (Acta Physiologiae Plantarum, 2018)

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

Growth promoting potential of fresh and stored Moringa oleifera leaf extracts in improving seedling vigor, growth and productivity of wheat crop - Shahbaz Khan; Shahzad Maqsood Ahmed Basra; Irfan Afzal; Muhammad Nawaz; Hafeez Ur Rehman (Environmental Science and Pollution Research, 2017)

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

Photosynthesis and growth response of maize (Zea mays L.) hybrids exposed to cadmium stress - Tasneem Akhtar; Muhammad Zia-ur-Rehman; Asif Naeem; Rab Nawaz; Shafaqat Ali; Ghulam Murtaza; Muhammad Aamer Maqsood; Muhammad Azhar; Hinnan Khalid; Muhammad Rizwan (Environmental Science and Pollution Research, 2017)

Prediction of Protein Submitochondrial Locations by Incorporating Dipeptide Composition into Chou’s General Pseudo Amino Acid Composition - Khurshid Ahmad; Muhammad Waris; Maqsood Hayat (The Journal of Membrane Biology, 2016)

Mapping QTL associated with remobilization of zinc from vegetative tissues into grains of barley (Hordeum vulgare) - Shahid Hussain; Zed Rengel; Seyed A. Mohammadi; Asghar Ebadi-Segherloo; Muhammad A. Maqsood (Plant and Soil, 2016)

iRSpot-GAEnsC: identifing recombination spots via ensemble classifier and extending the concept of Chou’s PseAAC to formulate DNA samples - Muhammad Kabir; Maqsood Hayat (Molecular Genetics and Genomics, 2016)

Interactive effect of cobalt and nitrogen on growth, nodulation, yield and protein content of field grown pea - Fahmida Mir Akbar; Mohsin Zafar; Abdul Hamid; Maqsood Ahmed; Abdul Khaliq; Muhammad Riaz Khan; Zahid ur Rehman (Horticulture, Environment, and Biotechnology, 2013)

Biofortification and estimated human bioavailability of zinc in wheat grains as influenced by methods of zinc application - Shahid Hussain; Muhammad Aamer Maqsood; Zed Rengel; Tariq Aziz (Plant and Soil, 2012)

Mineral bioavailability in grains of Pakistani bread wheat declines from old to current cultivars - Shahid Hussain; Muhammad Aamer Maqsood; Zed Rengel; Muhammad Khawar Khan (Euphytica, 2012)